2020
DOI: 10.1111/cas.14406
|View full text |Cite
|
Sign up to set email alerts
|

Corrected human papillomavirus vaccination rates for each birth fiscal year in Japan

Abstract: In Japan, the serious adverse events after human papillomavirus (HPV) vaccination were widely reported in the media. The Ministry of Health, Labour and Welfare of Japan (MHLW) announced the suspension of the governmental recommendation of HPV vaccine in 2013, and the inoculation rate has since sharply declined. The estimated inoculation rate for each birth fiscal year (FY) announced by the MHLW and the actual numbers for each birth FY surveyed by local governments were very different. In particular, the cumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 8 publications
3
61
1
Order By: Relevance
“…We have already complained that the following efforts are needed as soon as possible: (1): Provide opportunities for immunization for younger women who are already older than the normally targeted ages of 12–16 years, this is because they were not immunized during the vaccine recommendation hiatus, and thus are at greater risk, (2): Start inoculating young boys, (3): Introduce the newer, more comprehensive nine-valent HPV vaccine, (4): Enhance local, national and public health recommendations for cervical cancer screening as a way to reduce the health damage incurred by the suspension of recommendation, (5): Create a special national action plan to re-promote HPV immunization, and (6): Provide more accurate and pro-vaccine information for the media to report [ 26 ]. We have begun to recognize the harsh reality that a girl born in Japan in the very near future may eventually die of cervical cancer as a direct result of MHLW’s suspension of its recommendation for HPV vaccination, and its decision to continue that suspension over these seven long years [ 8 , 27 , 28 ]. Medical institutions, educational institutions, governments, researchers, and the media should be working together hand-in-hand to reconsider the way they are each providing information to mothers—so that this tragedy-in-slow motion will not be repeated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already complained that the following efforts are needed as soon as possible: (1): Provide opportunities for immunization for younger women who are already older than the normally targeted ages of 12–16 years, this is because they were not immunized during the vaccine recommendation hiatus, and thus are at greater risk, (2): Start inoculating young boys, (3): Introduce the newer, more comprehensive nine-valent HPV vaccine, (4): Enhance local, national and public health recommendations for cervical cancer screening as a way to reduce the health damage incurred by the suspension of recommendation, (5): Create a special national action plan to re-promote HPV immunization, and (6): Provide more accurate and pro-vaccine information for the media to report [ 26 ]. We have begun to recognize the harsh reality that a girl born in Japan in the very near future may eventually die of cervical cancer as a direct result of MHLW’s suspension of its recommendation for HPV vaccination, and its decision to continue that suspension over these seven long years [ 8 , 27 , 28 ]. Medical institutions, educational institutions, governments, researchers, and the media should be working together hand-in-hand to reconsider the way they are each providing information to mothers—so that this tragedy-in-slow motion will not be repeated.…”
Section: Discussionmentioning
confidence: 99%
“…This suspension, now seven years since its announcement, remains in effect as of May 2020. As a result of the combined effects of repeated media reports of the alleged adverse events and MHLW’s consequential suspension of its active recommendation, Japan’s HPV vaccination rate for girls born since 2000 has dropped sharply [ 8 ]. Japan now lags conspicuously behind WHO’s strategy pillar of achieving a high national HPV vaccination rate.…”
Section: Introductionmentioning
confidence: 99%
“…The data used in the present study was modified from those shown in the MHLW council meeting 8 to reflect the real cumulative vaccination rate for each birth FY 9 . In summary, the cumulative initial vaccination rate for each birth year: Born in FY1994: 55.5%, Born in FY1995: 73.5%, Born in FY1996: 78.2%, Born in FY1997: 78.8%, Born in FY1998: 78.7%, Born in FY1999: 68.9%, born in FY2000: 14.3%, born in FY2001: 1.6%, born in FY2002: 0.4%, born in FY2003: 0.2%, born in FY2004: 0.1%, born in FY2005: 0.0%.…”
Section: Methodsmentioning
confidence: 99%
“…We compared the prevalence of HPV type-specific infection between FY2014 and FY2015–2017, that is, women registered in FY2014 (born in FY1993–1994) and registered in FY2015–2017 (born in FY1994–1997). The vaccination coverage in the OHPV generation was over 70% [ 6 ].…”
Section: Methodsmentioning
confidence: 99%